EFFECT OF α-TOCOPHEROL AND ASCORBIC ACIDS ON PERFORMANCE AND BLOOD IMMUNITY PROFILE OF MALE NATIVE MUSCOVY DUCK - Tugiyanti, E.; Zuprizal, Z.; Rusman, R.; Yuwanta, T.; Ismoyowati, I. (Diponegoro University, 2016)
The purpose of the research was to assess the effect of α-tocopherol and ascobic acids on the performance and immunity blood profile of male native Muscovy duck. The materials used were 84 male Muscovy ducks at 9 weeks old. The research used completely randomized design with 7 treatments. The treatments were E0C0 : basal diet without α-tocopherol and ascobic acids, E400: basal diet+ α-tocopherol 400IU, E600: basal diet+α-tocopherol 600IU, C400: basal diet+ascorbic acid 400mg/kg, C600: basal diet+ascorbic acid 600mg/kg, E200C200: basal diet+α-tocopherol 200IU+ ascorbic acid 200mg/kg, and E300C300: basal diet+α-tocopherol 300IU+ ascorbic acid 300mg/kg. Each treatment was repeated 4 times and each replication consisted of 3 ducks. The observed variables were body weight, feed consumption, feed conversion ratio, packed cell volume (PCV), total of plasma protein (TPP), leucocyte count, basophil, heterophil, eosinophil, monocyte, lymphocytes count and heterophil/lymphocyte (H/L) ratio of Muscovy duck. The result indicated that E0C0, E400, E600, C400, C600, E200C200 and E300C300 had no significant difference in body weight, feed intake and feed conversion. There were significant effects on PCV, leucocyte count, percentage of heterophil and lymphocytes, but had no significant effect on eosinophil, monocyte and the H/L ratio. The C400 resulted a higher PCV count, percentage of heterophil, and H/L ratio. The C 600 produced the highest leucocyte count. In conclusion, the supplementation of ascorbic acid at 400 - 600 mg/kg feed ascorbic acid could improve theimmune profile, but could not improve the performance of Muscovy duck.